Spherical aluminum oxide loaded with rodlike nano CeO2-CuO compound and preparation method of spherical aluminum oxide
Through one-step calcination preparation method and oil ammonia column forming technology, spherical alumina loaded with rod-shaped nano CeO2-CuO composites solves the problems of complex preparation, uneven distribution and low strength in the prior art, and achieves efficient and uniform catalyst dispersion and strength improvement.
Patent Information
- Application Number
- CN202411856707.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-04
AI Technical Summary
The preparation process of existing spherical alumina supported catalysts is complicated, the catalyst distribution is uneven, the strength is low and the service life is short, resulting in a reduced catalytic efficiency.
By using one-step calcination preparation method, the rod-shaped nano CeO2-CuO composite precursor was directly mixed into the aluminum sol through oil ammonia column forming technology to form spherical alumina supported by rod-shaped nano CeO2-CuO composite.
The preparation process is simplified, the uniform dispersion and mechanical strength of the catalyst are improved, the service life is extended and the catalytic performance is improved.
Smart Images

Figure CN119746875A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material preparation, and in particular to a loaded rod-shaped nano CeO 2 Spherical alumina of -CuO composite and preparation method thereof. Background Art
[0002] p-Nitrophenol (4-NP) is a colorless to light yellow crystalline powder, mainly used in pesticides, medicines, dyes and other industries. But at the same time, 4-NP is also a common water pollutant, harmful to the environment, and a carcinogen and teratogen. On the other hand, p-aminophenol (4-AP) is an important organic chemical intermediate. Therefore, converting p-nitrophenol (4-NP) into p-aminophenol (4-AP) can turn waste into treasure and achieve higher economic and environmental value. In recent years, the method of using Cu-based materials as catalysts to reduce 4-NP to produce 4-AP using sodium borohydride has attracted widespread attention due to its high efficiency, good economy and low pollution. Cu-based catalysts mainly include elemental Cu, Cu 2 O and CuO. However, nanomaterials are prone to agglomeration and deactivation during use, so Cu-based catalysts are often loaded on other carriers.
[0003] Spherical alumina is often used as a catalyst carrier in industry, and the catalyst is loaded onto alumina microspheres by impregnation. This method requires the preparation of spherical alumina in advance, and then the catalyst is loaded onto the spherical alumina through steps such as immersion, drying and calcination. This method is complicated, and during the impregnation process, the catalyst is prone to agglomeration and uneven distribution. The catalyst blocks the pores on the surface of the alumina, resulting in a reduction in specific surface area and a decrease in catalytic efficiency.
[0004] The patent with publication number CN1762810A discloses a method for preparing magnetic micro-spherical alumina by one-step calcination, namely, dispersing the magnetic core precursor into aluminum sol, forming it by oil column molding method, and then washing, drying and calcining it once to obtain magnetic micro-spherical alumina. This method not only simplifies the operation steps, saves energy, and reduces the composition, but also makes the magnetic domain structure of the magnetic micro-spherical alumina more continuous after calcination.
[0005] The patent with the publication number CN113457661A discloses a catalyst for synthesizing acetonitrile by ammoniation of acetic acid and a preparation method thereof. The specific method is: mixing the powder obtained by neutralization of aluminum sulfate and sodium aluminate with pseudo-boehmite to make a glue, then mixing it evenly with a certain amount of transition metal and rare earth metal salts and a pore expander, then using an oil-ammonia column ball forming method to make small balls, calcining the small balls in an air atmosphere to obtain porous spherical alumina containing transition metal and rare earth metal oxides; then performing a hydration treatment, and drying to obtain a finished catalyst product.
[0006] Although the above methods improve the preparation efficiency, the spherical alumina used as a carrier is generally γ-Al2O3 and has a porous structure, which results in low strength. The alumina beads are easily broken during use, resulting in reduced catalyst recycling efficiency and shortened service life. Therefore, it is necessary to develop an alumina-loaded copper-based catalyst with a simple preparation method, good performance and the ability to improve the strength of alumina microspheres. Summary of the invention
[0007] In order to solve the above problems, the present invention proposes a rod-shaped nano CeO 2 -CuO composite spherical alumina preparation method, wherein the rod-shaped composite can play a reinforcing role on the spherical alumina. The method proposed by the present invention solves the problems of the existing spherical alumina supported catalyst, such as complicated preparation process, uneven catalyst distribution, low strength and short service life. In addition, CeO 2 It has a good synergistic effect with CuO and can enhance the catalytic activity of CuO.
[0008] In order to achieve the above object, the present invention adopts the following technical solutions:
[0009] A rod-shaped nano CeO 2 The preparation method of spherical alumina of -CuO composite specifically comprises the following steps:
[0010] Step 1, preparation of aluminum sol:
[0011] Take pseudo-boehmite and add it to water, stir and dissolve it to form a white alumina suspension, add nitric acid dropwise to the alumina suspension, then add distilled water and continue stirring to form an aluminum sol;
[0012] Step 2: Preparation of rod-shaped nano-CeO 2 -CuO composite precursor and mixed slurry:
[0013] Take one or two or more of cerium chloride, cerium nitrate, and ammonium cerium sulfate, mix them in water to dissolve, then take sodium citrate and dissolve them in water, mix the two mixed solutions evenly by ultrasonication, then add distilled water to dilute, transfer them into a conical flask, put them in an oven for aging, then wash the precipitate with distilled water and anhydrous ethanol, and dry them to obtain a cerium-containing powder;
[0014] Take one of copper sulfate, copper nitrate and copper chloride, dissolve it in anhydrous ethanol to obtain a copper-containing solution, add the dried cerium-containing powder into the copper-containing solution and stir, then heat and evaporate it with an electric heating plate to obtain rod-shaped nano CeO 2 -CuO complex precursor;
[0015] The obtained rod-shaped nano-CeO 2-CuO composite precursor is ground and added to the aluminum sol prepared in step 1, and stirred evenly to prepare a mixed slurry;
[0016] Step 3, oil-ammonia column formation: the mass concentration of ammonia water is 5-30%, the height of the ammonia water layer is 5-25 cm, the oil layer is one of kerosene, lubricating oil, and diesel, the oil layer height is 5-10 cm, the oil layer is above the ammonia water layer, and the oil-ammonia column is formed. 2 -CuO composite precursor mixed slurry into the ball dropper, and the rod-shaped nano CeO 2 -CuO composite precursor mixed slurry is dripped into the oil-ammonia column, and the ball first passes through the oil layer and then falls into the ammonia water layer;
[0017] Step 4, curing, drying, and calcining: pour the dropwise prepared small balls together with the ammonia water in the oil-ammonia column into a conical flask for curing for 24 to 96 hours, take them out and wash them with anhydrous ethanol, dry them at 50 to 90°C for 12 to 36 hours, then place them in a corundum crucible, and calcine them at 350 to 650°C for 2 to 4 hours in a tubular furnace with nitrogen or argon gas to obtain rod-shaped nano CeO 2 Spherical alumina of -CuO composite.
[0018] Further, the specific method of step 1 is as follows: 40-100 g of pseudo-boehmite is added to water, stirred and dissolved to form a white suspension, 15 mL of 9.6-51.2 wt% nitric acid is added dropwise to the alumina suspension, and then 10-225 mL of distilled water is added and stirred continuously to prepare Al 2 O 3 The solution has a mass content of 19.23-24.62%.
[0019] Furthermore, in step 2, 4.5-10 mmol of one or two or more of cerium chloride, cerium nitrate, and ammonium cerium sulfate are mixed and added to 20 mL of water to dissolve, 4.5-10 mmol of sodium citrate is added to 20 mL of water to dissolve, the above two mixed solutions are evenly mixed by ultrasound, and then 20 mL of distilled water is added to dilute, the oven temperature is 60°C, and the aging is carried out for 72-96 hours. The dried cerium-containing powder is added to the copper-containing solution and stirred for 8-15 hours, Ce:Cu=5:1-5:5, Ce:sodium citrate=1:1.
[0020] Furthermore, in step 2, ammonium cerium nitrate and cerium chloride are preferred.
[0021] Furthermore, in step 3, the diameter of the dropper needle of the ball dropper is 2 to 5 mm, the distance between the needle and the oil layer of the oil-ammonia column is 2 to 5 cm, and the ball dropping speed is 3 to 10 d / s.
[0022] Furthermore, in step 3, the height of the aqueous ammonia layer is preferably 10 to 20 cm, and the oil layer is preferably kerosene.
[0023] Furthermore, in step 4, the rod-shaped nano CeO 2 -CuO composite accounts for 2.8-10.2wt% of spherical alumina and rod-shaped nano-CeO 2 -CuO composites include fibers, particles, tubes, and flakes.
[0024] Furthermore, in step 4, nitrogen is preferably used, the sintering temperature is preferably 400°C, and the heating rate is: room temperature to 200°C, heating at 10°C / min, and from 200°C to the maximum temperature, heating at 2°C / min.
[0025] According to the above-mentioned rod-shaped nano CeO 2 Preparation method of spherical alumina of -CuO composite prepared by loaded rod-shaped nano CeO 2 Spherical alumina of -CuO composite.
[0026] Loaded rod-shaped nano CeO 2 Spherical alumina with -CuO complex is used for catalytic reduction of nitroaromatic organic substances and dye organic substances.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) The rod-shaped nano-CeO was prepared by a one-step calcination method. 2 The spherical alumina beads of the -CuO complex greatly shorten the preparation process and save costs. The catalyst precursor is directly mixed in the aluminum-containing slurry, which is conducive to the uniform dispersion of the catalyst in the carrier.
[0029] (2) Rod-shaped nano-CeO 2 It not only improves the catalytic performance of the CuO catalyst, but also improves the mechanical strength of the alumina balls. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The loaded rod-shaped nano CeO prepared in Example 4 of the present invention 2 -XRD spectrum of spherical alumina of CuO composite;
[0031] Figure 2 The rod-shaped nano CeO prepared in Example 4 of the present invention 2 Physical photograph of spherical alumina-CuO composite. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0033] Unless otherwise specified, all reagents used in the following examples were of analytical grade and commercially available chemical reagents.
[0034] A rod-shaped nano CeO 2 The preparation method of spherical alumina of -CuO composite specifically comprises the following steps:
[0035] Step 1, preparation of aluminum sol:
[0036] Take 40-100g of pseudo-boehmite and add it to water, stir and dissolve to form a white suspension, take 15mL of 9.6-51.2wt% nitric acid, add it dropwise to the alumina suspension, then add 10-225mL of distilled water and continue stirring to prepare Al 2 O 3 Aluminum sol having a mass content of 19.23-24.62%;
[0037] Step 2: Preparation of rod-shaped nano-CeO 2 -CuO composite precursor and mixed slurry:
[0038] Take 4.5-10mmol of one or two or more of cerium chloride, cerium nitrate, and ammonium cerium sulfate, mix them, add 20mL of water to dissolve, take 4.5-10mmol of sodium citrate, add 20mL of water to dissolve, mix the above two mixed solutions evenly by ultrasonication, then add 20mL of distilled water to dilute, transfer them into a conical flask, put them in an oven for aging at 60°C for 72-96h, then wash and dry the precipitate with distilled water and anhydrous ethanol to obtain a cerium-containing powder;
[0039] Take one of copper sulfate, copper nitrate and copper chloride, dissolve it in anhydrous ethanol to obtain a copper-containing solution, add the dried cerium-containing powder into the copper-containing solution and stir for 8 to 15 hours, Ce:Cu=5:1~5:5, Ce:sodium citrate=1:1, then heat and evaporate to dryness with an electric heating plate to obtain rod-shaped nano CeO 2 -CuO complex precursor;
[0040] The obtained rod-shaped nano-CeO 2 -CuO composite precursor is ground and added to the aluminum sol prepared in step 1, and stirred evenly to prepare a mixed slurry;
[0041] Step 3, oil-ammonia column formation: the mass concentration of ammonia water is 5-30%, the height of the ammonia water layer is 5-25 cm, the oil layer is one of kerosene, lubricating oil, and diesel, the oil layer height is 5-10 cm, the oil layer is above the ammonia water layer, and the oil-ammonia column is formed. 2 -CuO composite precursor slurry is placed in a ball dropper, the diameter of the dropper needle of the ball dropper is 2-5 mm, the distance between the needle and the oil layer of the oil-ammonia column is 2-5 cm, the ball drop speed is 3-10 d / s, and the rod-shaped nano CeO 2 -CuO composite precursor slurry is dripped into the oil-ammonia column, and the pellets first pass through the oil layer and then fall into the ammonia water layer;
[0042] Step 4, curing, drying, and calcining: pour the dropwise prepared small balls together with the ammonia water in the oil-ammonia column from the oil-ammonia column into an inverted conical flask for curing for 24 to 96 hours, take them out and wash them with anhydrous ethanol, dry them at 50 to 90°C for 12 to 36 hours, then place them in a corundum crucible, and calcine them at 350 to 650°C in a tubular furnace with nitrogen or argon for 2 to 4 hours. The heating rate is: room temperature to 200°C, 10°C / min heating, 200°C to the highest temperature, 2°C / min heating, to prepare rod-shaped nano CeO 2 Spherical alumina of -CuO composite.
[0043] Rod-shaped nano CeO 2 -CuO composite accounts for 2.8-10.2wt% of spherical alumina and rod-shaped nano-CeO 2 -CuO composites include fibers, particles, tubes, and flakes.
[0044] Example 1
[0045] A rod-shaped nano CeO 2 The preparation method of spherical alumina of -CuO composite specifically comprises the following steps:
[0046] (1) Preparation of aluminum sol: 40 g of pseudo-boehmite powder was added to 60 mL of water and stirred to dissolve to form a white suspension. 15 mL of 9.6 wt % nitric acid was added dropwise to the alumina suspension. 10 mL of distilled water was added and stirred for 2 h to prepare Al2O3 sol. 2 O 3 The calculated mass concentration of aluminum sol is 24.62%.
[0047] (2) Preparation of rod-shaped nano-CeO 2-CuO composite precursor and mixed slurry: Take 4.5mmol of cerium nitrate heptahydrate, add 20mL of water to dissolve, then take 4.5mmol of sodium citrate and add 20mL of water to dissolve, mix the two evenly by ultrasonication, then add 20mL of distilled water to dilute, ultrasonication evenly, transfer to a conical flask, put in an oven and age at 60°C for 72h, wash the precipitate with distilled water and anhydrous ethanol, and dry it to obtain cerium-containing powder; take 0.9mmol of copper nitrate trihydrate, add 10mL of anhydrous ethanol to dissolve, add the dried cerium-containing powder to the copper-containing solution, stir for 10h, then heat and evaporate to dryness at 60°C with an electric heating plate, and obtain rod-shaped nano CeO 2 -CuO composite precursor was ground, dissolved in 15 mL of water, added to the aluminum sol in step (1), and stirred evenly to prepare a mixed slurry. 2 -CuO composite precursor, the molar ratio of Ce:Cu is 5:1, and Ce:sodium citrate is 1:1.
[0048] (3) Oil-ammonia injection molding: The mass concentration of ammonia water is 10%, the height of the ammonia water layer is 10 cm, and the oil layer is kerosene with a height of 5 cm. The oil layer is located above the ammonia water layer to form an oil-ammonia column. The rod-shaped nano CeO prepared in step (2) is placed in the 2 -CuO composite precursor mixed slurry was placed in a ball dropper, the dropper needle had a diameter of 3mm, the needle was 3cm away from the kerosene liquid surface of the oil-ammonia column, the ball drop speed was 5d / s, and the rod-shaped nano CeO in the ball dropper was started. 2 -CuO composite precursor mixed slurry is dropped into the oil-ammonia column, and the small balls first pass through the kerosene layer and then fall into the ammonia water layer.
[0049] (4) Curing, drying, and calcining: Pour the prepared small balls together with the ammonia water in the oil-ammonia column into a conical flask for curing for 72 hours. After taking out, wash it with anhydrous ethanol for 3 times and dry it in an oven at 60°C for 12 hours. The dried sample is placed in a corundum crucible, and in a tube furnace, nitrogen is introduced, and the temperature is raised to 200°C at 10°C / min, and then raised to 350°C at 2°C / min, and kept at this temperature for 2 hours to obtain rod-shaped nano-CeO 2 Spherical alumina of -CuO composite. Rod-shaped nano-CeO 2 The mass percentage of the -CuO composite in the spherical alumina is 2.8%, and the average crushing strength is measured to be 61.68N.
[0050] Comparative Example 1
[0051] A method for preparing spherical aluminum oxide
[0052] Keeping other conditions in Example 1 unchanged, removing step (2), adding the aluminum sol in step (1) directly to the ball dropper in step (3) for ball dropping, and keeping other conditions unchanged, the obtained sample has an average crushing strength of 47.69N. By comparing Example 1 with Comparative Example 1, the rod-shaped nano CeO 2 -CuO composite, the crushing strength of spherical alumina is enhanced by 29.34%.
[0053] Example 2
[0054] A rod-shaped nano CeO 2 The preparation method of spherical alumina of -CuO composite specifically comprises the following steps:
[0055] (1) Preparation of aluminum sol: 40 g of pseudo-boehmite powder was added to 60 mL of water and stirred to dissolve to form a white suspension. 15 mL of 19.2 wt% nitric acid was added dropwise to the alumina suspension. 45 mL of distilled water was added and stirred for 2 h to prepare Al2O3 sol. 2 O 3 The calculated mass concentration of aluminum sol is 19.23%.
[0056] (2) Preparation of rod-shaped nano-CeO 2 -CuO composite precursor and mixed slurry: Take 5mmol of ammonium cerium nitrate, add 20mL of water to dissolve, then take 5mmol of sodium citrate and add 20mL of water to dissolve, mix the two evenly by ultrasonication, then add 20mL of distilled water to dilute, ultrasonication evenly, transfer to a conical flask, put it in an oven and age it at 60℃ for 72h, wash the precipitate with distilled water and anhydrous ethanol, and dry it to obtain cerium-containing powder. Take 2mmol of copper sulfate pentahydrate, add 10mL of anhydrous ethanol to dissolve, add the dried cerium-containing powder to the copper-containing solution, stir for 12h, then heat and evaporate to dryness at 60℃ on an electric heating plate, and obtain rod-shaped nano CeO 2 -CuO composite precursor was ground and dissolved in 60 mL of water, added to the aluminum sol in step (1), and stirred evenly to prepare a mixed slurry. 2 -CuO composite precursor, the molar ratio of Ce:Cu is 5:2, and Ce:sodium citrate is 1:1.
[0057] (3) Oil-ammonia injection molding: The mass concentration of ammonia water is 15%, the height of the ammonia water layer is 10 cm, and the oil layer is lubricating oil with a height of 6 cm. The oil layer is located above the ammonia water layer to form an oil-ammonia column. The rod-shaped nano CeO prepared in step (2) is 2 -CuO composite precursor mixed slurry was placed in a ball dropper, the dropper needle had a diameter of 3mm, the needle was 2cm away from the lubricating oil surface of the oil-ammonia column, the ball drop speed was 3d / s, and the rod-shaped nano CeO in the ball dropper was started.2 -CuO composite precursor mixed slurry is dropped into the oil-ammonia column, and the ball first passes through the lubricating oil layer and then falls into the ammonia water layer.
[0058] (4) Curing, drying, and calcining: Pour the prepared small balls together with the ammonia water in the oil-ammonia column into a conical flask for curing for 84 hours. After taking out, wash it with anhydrous ethanol for 3 times and dry it in an oven at 60°C for 24 hours. The dried sample is placed in a corundum crucible, and in a tube furnace, argon is introduced, and the temperature is raised to 200°C at 10°C / min, and then raised to 500°C at 2°C / min, and kept at this temperature for 2 hours to obtain rod-shaped nano-CeO 2 Spherical alumina of -CuO composite. Rod-shaped nano-CeO 2 The mass percentage of the -CuO composite in the spherical alumina is 3.3%, and the average crushing strength is measured to be 78.87N.
[0059] Comparative Example 2
[0060] A method for preparing spherical aluminum oxide
[0061] Keeping other conditions in Example 2 unchanged, removing step (2), adding the aluminum sol in step (1) directly to the ball dropper in step (3), and dropping the ball, the other conditions remain unchanged. The sample was obtained, and the average crushing strength was measured to be 70.06N. By comparing Example 2 with Comparative Example 2, the rod-shaped nano CeO 2 -CuO composite, the crushing strength of spherical alumina is enhanced by 12.57%.
[0062] Example 3
[0063] A rod-shaped nano CeO 2 The preparation method of spherical alumina of -CuO composite specifically comprises the following steps:
[0064] (1) Preparation of aluminum sol: 60 g of pseudo-boehmite powder was added to 60 mL of water and stirred to dissolve to form a white suspension. 15 mL of 19.15 wt% nitric acid was added dropwise to the alumina suspension. 75 mL of distilled water was added and stirred for 2 h to prepare Al2O3 sol. 2 O 3 The calculated mass concentration of aluminum sol is 21.98%.
[0065] (2) Preparation of rod-shaped nano-CeO 2-CuO composite precursor and mixed slurry: Take 10mmol of cerium sulfate tetrahydrate, add 20mL of water to dissolve, then take 10mmol of sodium citrate and add 20mL of water to dissolve, mix the two evenly by ultrasonic, then add 20mL of distilled water to dilute, ultrasonically evenly, transfer to a conical flask, put it in an oven and age it at 60℃ for 80h, wash and dry the precipitate with distilled water and anhydrous ethanol to obtain cerium-containing powder. Take 6mmol of copper sulfate pentahydrate, add 10mL of anhydrous ethanol to dissolve, add the dried cerium-containing powder to the copper-containing solution, stir for 8h, then heat and evaporate to dryness at 70℃ on an electric heating plate, and obtain rod-shaped nano CeO 2 -CuO composite precursor was ground and dissolved in 110 mL of water, then added to the aluminum sol in step (1) and stirred evenly to prepare a mixed slurry. 2 -CuO composite precursor, Ce:Cu molar ratio is 5:3, Ce:sodium citrate = 1:1
[0066] (3) Oil-ammonia injection molding: The mass concentration of ammonia water is 12%, and the height of the ammonia water layer is 20 cm. The oil layer is diesel oil, and the height is 8 cm. The oil layer is located above the ammonia water layer, forming an oil-ammonia column. The slurry in step (2) is placed in a ball dropper. The dropper needle has a diameter of 3 mm, and the needle is 3 cm away from the diesel liquid level of the oil-ammonia column. The ball drop speed is 6 d / s. The rod-shaped nano CeO in the ball dropper is started. 2 -CuO composite precursor mixed slurry is dropped into the oil-ammonia column, and the small balls first pass through the diesel layer and then fall into the ammonia layer.
[0067] (4) Curing, drying, and calcining: The small balls that have been dripped are poured into a conical flask together with the ammonia water in the oil-ammonia column and cured for 60 hours. After being taken out, they are washed with anhydrous ethanol 4 times and dried in an oven at 60°C for 24 hours. The dried sample is placed in a corundum crucible, put into a tube furnace, and argon is introduced. The temperature is raised to 200°C at 10°C / min, and then raised to 650°C at 2°C / min. The temperature is kept at this temperature for 2 hours to obtain the final product. 2 The mass percentage of the -CuO composite in the spherical alumina is 4.8%, and the average crushing strength is measured to be 66.97N.
[0068] Comparative Example 3
[0069] A method for preparing spherical aluminum oxide
[0070] Keeping other conditions in Example 3 unchanged, removing step (2), adding the aluminum sol in step (1) directly to the ball dropper in step (3), and dropping the ball, the other conditions remain unchanged. The sample was obtained, and the average crushing strength was measured to be 59.84N. By comparing Example 3 with Comparative Example 3, the rod-shaped nano CeO 2-CuO composite, the crushing strength of spherical alumina is enhanced by 11.92%.
[0071] Example 4
[0072] A rod-shaped nano CeO 2 The preparation method of spherical alumina of -CuO composite specifically comprises the following steps:
[0073] (1) Preparation of aluminum sol: 80 g of pseudo-boehmite powder was added to 60 mL of water and stirred to dissolve to form a white suspension. 15 mL of 51.2 wt% nitric acid was added dropwise to the alumina suspension. 125 mL of distilled water was added and stirred for 2 h to prepare Al2O3 sol. 2 O 3 The calculated mass concentration of aluminum sol is 21.98%.
[0074] (2) Preparation of rod-shaped nano-CeO 2 -CuO composite precursor and mixed slurry: Take 10mmol of cerium nitrate heptahydrate and 15mmol of ammonium cerium nitrate, mix them, add 20mL of water to dissolve, then take 25mmol of sodium citrate and add 20mL of water to dissolve, mix the two evenly by ultrasonic, then add 20mL of distilled water to dilute, ultrasonically evenly, transfer to a conical flask, put it in an oven and age it at 60℃ for 72h, wash and dry the precipitate with distilled water and anhydrous ethanol to obtain cerium-containing powder. Take 25mmol of cupric chloride dihydrate, add 10mL of anhydrous ethanol to dissolve, add the dried cerium-containing powder to the copper-containing solution, stir for 10h, then heat and evaporate to dryness at 60℃ on an electric heating plate, and obtain rod-shaped nano CeO 2 -CuO composite precursor was ground and dissolved in 600 mL of water, then added to the aluminum sol in step (1) and stirred evenly to prepare a mixed slurry. 2 -CuO composite precursor, the molar ratio of Ce:Cu is 5:5, and Ce:sodium citrate is 1:1.
[0075] (3) Oil-ammonia injection molding: The mass concentration of ammonia water is 10%, and the height of the ammonia water layer is 15 cm. The oil layer is kerosene, and the height is 10 cm. The oil layer is located above the ammonia water layer, forming an oil-ammonia column. The slurry prepared in step (2) is placed in a ball dropper. The dropper needle has a diameter of 3 mm, and the needle is 3 cm away from the kerosene liquid level of the oil-ammonia column. The ball drop speed is 5 d / s, and the rod-shaped nano CeO in the ball dropper is started. 2 -CuO composite precursor mixed slurry is dropped into the oil-ammonia column, and the small balls first pass through the kerosene layer and then fall into the ammonia water layer.
[0076] (4) Curing, drying, and calcining: Pour the prepared small balls together with the ammonia water in the oil-ammonia column into a conical flask and cure for 84 hours. After taking out, wash it with anhydrous ethanol three times and dry it in an oven at 60°C for 30 hours. Put the dried sample in a corundum crucible, introduce nitrogen in a tube furnace, heat it to 200°C at 10°C / min, and then heat it to 450°C at 2°C / min. Keep it warm for 2 hours to obtain the final product. 2 The mass percentage of the spherical alumina is 10.2%. The average crushing strength is 51.64N.
[0077] Figure 1 This is a rod-shaped nano CeO loaded in Example 4 of the present invention. 2 Preparation method of spherical alumina of -CuO composite prepared by loaded rod-shaped nano CeO 2 XRD spectrum of spherical alumina of -CuO composite. Figure 1 It can be seen that the product contains Al 2 O 3 、CeO 2 and CuO peaks, indicating that rod-shaped nano-CeO loaded with this method was successfully prepared 2 -Spherical alumina with CuO catalyst.
[0078] Figure 2 The rod-shaped nano CeO prepared in Example 4 of the present invention 2 -CuO composite spherical alumina real picture, from Figure 2 It can be seen that the samples prepared by this method have good sphericity and uniform size.
[0079] Comparative Example 4
[0080] A method for preparing spherical aluminum oxide
[0081] Keeping other conditions in Example 4 unchanged, removing step (2), adding the aluminum sol in step (1) directly to the ball dropper in step (3), and dropping the ball, the other conditions remain unchanged. The sample was obtained, and the average crushing strength was measured to be 38.35N. By comparing Example 4 with Comparative Example 4, the rod-shaped nano CeO 2 -CuO composite, the crushing strength of spherical alumina is enhanced by 34.65%.
[0082] Example 5
[0083] A rod-shaped nano CeO 2 The preparation method of spherical alumina of -CuO composite specifically comprises the following steps:
[0084] (1) Preparation of aluminum sol: 100 g of pseudo-boehmite powder was added to 60 mL of water and stirred to dissolve to form a white suspension. 15 mL of 38.4 wt% nitric acid was added dropwise to the alumina suspension. 225 mL of distilled water was added and stirred for 2 h to prepare Al2O3 sol. 2 O 3 The calculated mass concentration of aluminum sol is 19.23%.
[0085] (2) Preparation of rod-shaped nano-CeO 2 -CuO composite precursor and mixed slurry: Take 5mmol of cerium nitrate heptahydrate and 5mmol of cerium sulfate tetrahydrate, mix them, add 20mL of water to dissolve, then take 10mmol of sodium citrate and add 20mL of water to dissolve, mix the two evenly by ultrasonic, then add 20mL of distilled water to dilute, ultrasonically evenly, transfer to a conical flask, put it in an oven and age it at 60℃ for 96h, wash and dry the precipitate with distilled water and anhydrous ethanol to obtain cerium-containing powder. Take 8mmol of dihydrate and copper chloride, add 10mL of anhydrous ethanol to dissolve, add the dried cerium-containing powder to the copper-containing solution, stir for 15h, then heat and evaporate to dryness at 75℃ on an electric heating plate, and obtain rod-shaped nano CeO 2 -CuO composite precursor was ground and dissolved in 40 mL of water, then added to the aluminum sol in step (1) and stirred evenly to prepare a mixed slurry. 2 -CuO composite precursor, the molar ratio of Ce:Cu is 5:4, and Ce:sodium citrate is 1:1.
[0086] (3) Oil-ammonia injection molding: The mass concentration of ammonia water is 8.6%, and the height of the ammonia water layer is 23 cm. The oil layer is lubricating oil, and the height is 10 cm. The oil layer is located above the ammonia water layer, forming an oil-ammonia column. The slurry prepared in step (2) is placed in a ball dropper. The dropper needle has a diameter of 3 mm, and the needle is 5 cm away from the lubricating oil level of the oil-ammonia column. The ball drop speed is 10 d / s, and the rod-shaped nano CeO in the ball dropper is started. 2 -CuO composite precursor mixed slurry is dropped into the oil-ammonia column, and the ball first passes through the lubricating oil layer and then falls into the ammonia water layer.
[0087] (4) Curing, drying, and calcining: Pour the prepared small balls together with the ammonia water in the oil-ammonia column into a conical flask and cure for 96 hours. After taking out, wash it with anhydrous ethanol three times and dry it in an oven at 60°C for 24 hours. The dried sample is placed in a corundum crucible, and in a tube furnace, argon is introduced, and the temperature is raised to 200°C at 10°C / min, and then raised to 400°C at 2°C / min, and kept at this temperature for 2 hours to obtain the final product. 2 The mass percentage of the -CuO composite in the spherical alumina is 3.1%. The average crushing strength is 77.07N.
[0088] Comparative Example 5
[0089] A method for preparing spherical aluminum oxide
[0090] Keeping other conditions in Example 5 unchanged, removing step (2), adding the aluminum sol in step (1) directly to the ball dropper in step (3), and dropping the ball, the other conditions remain unchanged. The sample was obtained, and the average crushing strength was measured to be 62.47N. By comparing Example 5 with Comparative Example 5, the rod-shaped nano CeO 2 -CuO composite, the crushing strength of spherical alumina is enhanced by 23.37%.
[0091] The following are Examples 1-5 and Comparative Examples 1-5. 15 samples were taken from each example to test their crushing strength. The results are shown in Table 1:
[0092] Table 1 Average crushing strength of Examples 1-5 and Comparative Examples 1 to 5 (unit / N)
[0093]
[0094] It can be seen from Table 1 that the rod-shaped nano CeO prepared in Examples 1-5 2 -CuO composite spherical alumina, its crushing strength is higher than the corresponding comparative example, indicating that the rod-shaped nano CeO 2 -CuO can enhance the strength of alumina pellets.
[0095] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites, characterized in that: The specific steps include: Step 1, preparation of aluminum sol: Take pseudo-boehmite and add it to water, stir and dissolve it to form a white alumina suspension, add nitric acid dropwise to the alumina suspension, then add distilled water and continue stirring to form an aluminum sol; Step 2, preparing rod-shaped nano CeO2-CuO composite precursor and mixed slurry: Take one or two or more of cerium chloride, cerium nitrate, and ammonium cerium sulfate, mix them in water to dissolve, then take sodium citrate and dissolve them in water, mix the two mixed solutions evenly by ultrasonication, then add distilled water to dilute, transfer them into a conical flask, put them in an oven for aging, then wash the precipitate with distilled water and anhydrous ethanol, and dry them to obtain a cerium-containing powder; Take one of copper sulfate, copper nitrate and copper chloride, dissolve it in anhydrous ethanol to obtain a copper-containing solution, add the dried cerium-containing powder into the copper-containing solution and stir, then heat and evaporate it with an electric heating plate to obtain a rod-shaped nano CeO2-CuO composite precursor; Grind the obtained rod-shaped nano CeO2-CuO composite precursor and add it to the aluminum sol prepared in step 1, stir evenly, and prepare a mixed slurry; Step 3, oil-ammonia column formation: the mass concentration of ammonia water is 5-30%, the height of the ammonia water layer is 5-25 cm, the oil layer is one of kerosene, lubricating oil, and diesel, the oil layer height is 5-10 cm, the oil layer is above the ammonia water layer, and the oil-ammonia column is formed. The rod-shaped nano CeO2-CuO complex precursor mixed slurry prepared in step 2 is placed in a ball dropper, and the rod-shaped nano CeO2-CuO complex precursor mixed slurry in the ball dropper is dripped into the oil-ammonia column, and the small ball first passes through the oil layer and then falls into the ammonia water layer; Step 4, curing, drying and calcining: pour the drop-formed small balls together with the ammonia water in the oil-ammonia column from the oil-ammonia column into a conical flask for curing for 24 to 96 hours, take them out and wash them with anhydrous ethanol, dry them at 50 to 90°C for 12 to 36 hours, then place them in a corundum crucible, and sinter them at 350 to 650°C in a tubular furnace with nitrogen or argon for 2 to 4 hours to obtain spherical alumina loaded with rod-shaped nano-CeO2-CuO complexes.
2. The method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites according to claim 1, characterized in that: The specific method of step 1 is as follows: 40-100 g of pseudo-boehmite is added to water, stirred to dissolve, and a white suspension is formed. 15 mL of 9.6-51.2 wt% nitric acid is added dropwise to the alumina suspension, and then 10-225 mL of distilled water is added and stirred continuously to prepare a solution with a mass content of 19.23-24.62% of Al2O3.
3. The method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites according to claim 1, characterized in that: In step 2, 4.5-10 mmol of one or two or more of cerium chloride, cerium nitrate, and ammonium cerium sulfate are mixed and added to 20 mL of water to dissolve, 4.5-10 mmol of sodium citrate is added to 20 mL of water to dissolve, the above two mixed solutions are mixed evenly by ultrasound, and then 20 mL of distilled water is added to dilute, the oven temperature is 60° C., and the aging is performed for 72-96 hours. The dried cerium-containing powder is added to the copper-containing solution and stirred for 8-15 hours, Ce:Cu=5:1-5:5, Ce:sodium citrate=1:
1.
4. The method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites according to claim 1, characterized in that: In step 2, ammonium cerium nitrate and cerium chloride are preferred.
5. The method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites according to claim 1, characterized in that: In step 3, the diameter of the dropper needle of the ball dropper is 2 to 5 mm, the distance between the needle and the oil layer of the oil-ammonia column is 2 to 5 cm, and the ball dropping speed is 3 to 10 d / s.
6. The method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites according to claim 1, characterized in that: In step 3, the height of the ammonia water layer is preferably 10 to 20 cm, and the oil layer is preferably kerosene.
7. The method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites according to claim 1, characterized in that: In step 4, the mass percentage of the rod-shaped nano CeO2-CuO composite to the spherical alumina is 2.8-10.2wt%, and the rod-shaped nano CeO2-CuO composite includes fibrous, granular, tubular, and flake shapes.
8. The method for preparing spherical alumina loaded with rod-shaped nano CeO2-CuO composites according to claim 1, characterized in that: In step 4, nitrogen is preferably used, the sintering temperature is preferably 400°C, and the heating rate is: room temperature to 200°C, heating at 10°C / min, and from 200°C to the maximum temperature, heating at 2°C / min.
9. Spherical alumina loaded with rod-shaped nano-CeO2-CuO composites prepared according to the method for preparing spherical alumina loaded with rod-shaped nano-CeO2-CuO composites according to any one of claims 1 to 8.
10. Use of spherical alumina loaded with rod-shaped nano CeO2-CuO composites, characterized in that: Spherical alumina loaded with rod-shaped nano-CeO2-CuO composites is used for the catalytic reduction of nitroaromatic organic substances and dye organic compounds.
Citation Information
Patent Citations
Catalyst for synthesis of acetonitrile by ammoniation of acetic acid and preparation method thereof
CN113457661A
One-step baking method for preparing magnetic microspheric alumina
CN1762810A
Cited By
CuO / CeO2 catalyst as well as preparation method and application thereof
CN119972097A